The Psychological Time Questionnaire: The psychometric qualities - Liniauskaitė, Audronė (Psichologija, 2007)
The psychological time – rather complicated area of psychological measurement due to complexity of object, ambiguity of the concepts, the lack of solid model and valid measurement method. The most researchers of this area stimulates the creation of the new methods of psychological time measurement, the individual differences are emphasized, which are linked with cultural, ethnics, religious peculiarities of society, prevailing system of values and even with economical level. The aim of the study is to create the psychological time questionnaire using empirical strategy. Questionnaire had been created in two phases. There were 119 statements in the first version. Statements were formulated on the basis of previous experience of investigations and psychological time parameters that were mentioned in scientific literature. Primal research had been accomplished after questioning 254 participants. By the mean of factorial analysis there were distinguished 29 questions, which comprised 6 scales: Time planning, Work time / leisure mixture, Time anxiety, Orientation to the past, Orientation to the future and Orientation to the present. 6 factors that were distinguished explained 55% of the variance. Cronbach alpha of distinguished scales varies from 0.602 (in the scale of Orientation to the present) to 0.812 (in the Work time / leisure mixture scale) 687 participants attended in the second research. 6 distinguished factors explain 57.86% of variance. After new obtained data had been analyzed, 4 meaningfully indiscreet factors were noticed. The first factor shows bewilderment of work time and leisure time areas, second factor – predisposition to plan time, and the third – time anxiety. Whereas in the fourth factor alongside the statements about the past, one factor, which is associated with the future appears. The statements, related with the orientation to the future, fall to the fifth factor, but there appears the statement of time anxiety and the statement “I often plan the future” fall into this factor with negative load. The sixth factor again has clearly predictable meaning – orientation to the present.So, we decided to remove two statements. Confirmative factorial analysis that was performed showed that propositions (statements) for the scales are selected adequately (χ2 = 1387.689, df = 309, p = .00, CFI = .84, TLI = .89, RMSEA = .07). The internal consistency indices of the final version of the scale are better than the first scale. Cronbach alpha varies from 0.657 (Orientation to the future) to 0.863 (Work time/leisure time mixture).
Keywords: Time Psychology; Psychological Time; Psychological Time Questionnaire